Evaluación de un programa de calificación para agentes educativos de la primera infancia. (2019)
This evaluative research has measured the implementation of the qualification program Hogares con Vivencias which was directed to educational early childhood agents. An evaluative qualitative research was conducted from the formative perspective. It was used as instruments: Guide of questions, observation records and accompanying protocols in Community households. The results demonstrate that the educational agents valued the implementation in a positive way, in a learning level changes are achieved in knowledge and intentions of change in practices were identified. The findings contribute to acknowledge the relevance of processes significance in qualification programs to educators.